Grazing behavior and production characteristics among cows differing in residual feed intake while grazing late season Idaho rangeland. (10th December 2019) - Sprinkle, James E; Taylor, J Bret; Clark, Patrick E; Hall, John B; Strong, Nicole K; Roberts-Lew, Meghan C
Abstract: The objectives were to determine whether cows previously classified during a postweaning test as either low or high residual feed intake (LRFI or HRFI ) differed in BW, BCS, and winter grazing activity while consuming poor-quality forage. Thirty Hereford × Angus (LRFI = 16; HRFI = 14) 2-yr-old mid- to late-gestation cows (pregnant with second calf) grazed sagebrush steppe for 78 d beginning 29 September 2015. BW and BCS were collected before and after grazing. Five cows of each RFI classification were fitted with global positioning system (GPS ) collars on 16 November 2015 with data collection commencing 3 d later and continuing for 25 d in a 323-ha pasture. The GPS units collected location coordinates every 2 min from which total daily travel distance (DTD ) was calculated. Visual counts for bite rate were obtained from collared cows over 8 d. Coordinate data, daily bite rate, BW, and BCS were analyzed as repeated measures using a mixed model, which included RFI group, day, and RFI group × day as fixed effects and cow within RFI group as the random effect. Change in BW and BCS was analyzed by ANOVA with RFI group as the main effect. Cow BCS and BW differed for both day ( P < 0 .0001) and day × RFI ( P < 0 .05). Body condition was less ( P < 0 .05) in LRFI cows at the beginning (5.8 ± 0.13 vs. 6.2 ± 0.14 BCS), but similar ( P = 0 .67) to HRFI at the end of the study (4.6 ± 0.13 vs. 4.6 ± 0.14). BW among the RFI groups did not differ ( P = 0 .20) prior to going to range. However, BW-change and BCS-change differed ( P < 0 .05) between RFI groups. Not only did the LRFI cows lose less BW (−50.0 ± 5.41 kg vs. −66.6 ± 5.78 kg) over the trial, they also were less variable with respect to BW loss. Cows did not differ ( P > 0 .21) by RFI for DTD or bite rate, but day was significant ( P < 0 .0001) with cows increasing bite rate as the season of year progressed (55.2 ± 5.63 bites/min for day 4 vs. 84.8 ± 5.32 bites/min for day 21) and increasing DTD as snow storms occurred. Although LRFI cows were leaner than HRFI cows at the commencement of the project, they lost less BW in a late season rangeland environment.